Проектування обладнання синергетичних процесів хімічної інженерії за моделями дослідження модернізації бурової установки - (:unkn) unknown (Національний технічний університет "Харківський політехнічний інститут", 2024)
У матеріалах статті розглянуті приклади розрахунків та вибору технологічного комплексу для буріння свердловини глибиною 5650 м, проаналізований комплекс механізації і часткової автоматизації спуско-підіймальних операцій при бурінні свердловин, встановлені переваги таких систем порівняно з установками, які не оснащені комплексом механізмів АСП. Проведено обґрунтування доцільності та економічної ефективності введення запропонованих технічних рішень з розробки пристрою для обмеження ходу талевого блоку бурової установки, запропоновані його принципова та електрична схеми, обґрунтовано технічну доцільність, розрахований економічний ефект від впровадження розробленої конструкції пристрою для обмеження ходу талевого блоку. Представлені складові розробленої методики розрахунку енергетичних витрат і витрат машинного часу при СПО підйомними комплексами, здійснено оцінку досконалості підйомних комплексів бурових установок з різним приводом за витратами машинного часу підйому бурильної колони за цикл буріння свердловини, оцінку досконалості підйомних комплексів бурових установок з різним приводом за енерговитратами на підйом бурильної колони за цикл проводки свердловини. In the materials of the article, examples of calculations and selection of a technological complex for drilling a well with a depth of 5650 m are considered, a complex of mechanization and partial automation of lowering and lifting operations during well drilling is analyzed, the advantages of such systems are established compared to installations that are not equipped with a complex of ASP mechanisms. The justification of the feasibility and economic efficiency of the introduction of the proposed technical solutions for the development of a device for limiting the movement of the melting unit of the drilling rig was carried out, its principle and electrical diagrams were proposed, the technical feasibility was substantiated, and the economic effect of the implementation of the developed design of the device for limiting the movement of the melting unit was calculated. The components of the developed methodology for calculating energy costs and machine time costs during SPO by lifting complexes are presented, an assessment of the perfection of lifting complexes of drilling rigs with different drives in terms of machine time costs of lifting a drill string for a well drilling cycle, an assessment of the perfection of lifting complexes of drilling rigs with different drives in terms of energy consumption rise of the drill string during the well drilling cycle. The materials of the article consider examples the calculation and the chosen technological complex for wells drilling with the depth of 5650 m, analyses the complex of mechanisms to mechanise and partially automate lowering-lifting operations while wells drilling and establishes advantages of such systems, comparing to the sets not equipped with the complex of mechanisms ALL.
Designing equipment for synergetic chemical engineering processes according to drilling rig modernization research models
Keywords: технологічний комплекс буріння; розрахунки; технічні рішення; технічна доцільність; методи; дослідження; technological complex of drilling; calculations; technical solutions; technical feasibility; methods; research